INVESTASI WAKAF UANG: STUDI KASUS PADA DOMPET DHUAFA DAN AL AZHAR PEDULI UMAT - Mariya Ulpah; Asep Saepudin Jahar (STES Islamic Village, 2019)
This study attempts to investigate the innovation model of cash waqf investment at business sectors. Various Investment has been conducting by the waqf board such as: Dompet Dhuafa through its subsidiary Tabung Wakaf Indonesia and Al-Azhar Peduli Umat. By conducting interview to many parties and documentation study this study finds that cash waqf contributes to improvement many sectors related to the poor such as: building health facilities, educational program, and economic program development for the needy.